Evaluation of antibacterial properties of novel phthalocyanines against Escherichia coli--comparison of analytical methods - Mikula, Premysl; Kalhotka, Libor; Jancula, Daniel; Zezulka, Stepan; Korinkova, Radka; Cerny, Jiri; Marsalek, Blahoslav; Toman, Petr (Journal of photochemistry and photobiology. B, Biology, 2014)
We analyzed antibacterial effects of several novel phthalocyanines against Escherichia coli and evaluated the suitability of flow cytometry for the detection of antibacterial effects of phthalocyanines in comparison with routinely used cultivation. After 3h of exposure under cool white light eight cationic phthalocyanines showed very high antibacterial activity in the concentration of 2.00 mg L(-1) and four of them were even efficient in the concentration of 0.20 mg L(-1). Antibacterial activity of neutral and anionic compounds was considerably lower or even negligible. No antibacterial effect was detected when bacteria were exposed without illumination. Binding affinity to bacterial cells was found to represent an important parameter influencing phthalocyanine antibacterial activity that can be modified by total charge of peripheral substituents and by the presence of suitable functional groups inside them. Agglomeration of cells observed in suspensions treated with a higher concentration of certain cationic phthalocyanines (the strongest binders to bacterial membrane) affected cytometric measurements of total cell counts, thus without appropriate pretreatment of the sample before analysis this parameter seems not to be fully valid in the evaluation of phthalocyanine antibacterial activity. Cytometric measurement of cell membrane integrity appears to be a suitable and even more sensitive parameter than cultivation.
Keywords: singletový kyslík; antibakteriální látky; světlo; Anti-Bacterial Agents; indoly; Singlet Oxygen; Escherichia coli; Light; průtoková cytometrie; fotosenzibilizující látky; Flow Cytometry; Photosensitizing Agents; Indoles